Analisis Pengaruh Gaya Kepemimpinan Partisipatif, Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Pt. Bank Bukopin Tbk. Cabang Klaten - Arifin, Syaiful, Basworo Dibyo, S.E., M.Si (2016)
This study aims to determine how the influence of participatory leadership style, motivation and discipline the performance of employees of PT. Bank Bukopin Tbk. Klaten branch. The subjects were employees of PT. Bank Bukopin Tbk. Klaten branch as much as 70 respondents. Data collection method that uses observation and questionnaires. Using validity and reliability test as a tool instrument, classic assumption test, multiple linear regression analysis, hypothesis testing partially (t-test) and simultaneous (f-test) and the coefficient of determination (R2) is used to get the accurate data ini order to draw a conclusion. The results show that the positive effect of leadership style on employee performance, motivation positive influence on employee performance, discipline of work has positive influence on employee performance. And it can be concluded that the style of leadership, motivation, and discipline significantly influence employee performance of PT. Bank Bukopin Tbk. Klaten branch. Key words: employee performance, participatory leadership style, motivation, work discipline.